(untitled) (Damascus University Journal of agriculture sciences, 2021)
This study investigated the distribution of available soil boron and its relationship with some soil properties in the soil collected from five agricultural stability areas of Homs Governorate. The number of samples was 41 and was taken on date 1/3/2014-1/7/2014, and the study was conducted at the Faculty of Agriculture, Al-Baath University. Available Boron was extracted by using hot water and determined using azomethine-H. The Available Boron in studies soils ranged from 0.437 to 2.198 mg kg-1 with an average of 0.893 mg kg-1. Correlation analysis showed that significant positive correlation between available B and each of EC (R= 0.739) and the organic matter of soil (R=0.618). The Linear regression equation showed that the available B was related significantly to the physico- chemical properties of studied soil.